COMPARING THE EFFICACY OF INTRAVENOUS CIPROFLOXACIN AND CEFTAZIDIME FOR TREATING SPONTANEOUS BACTERIAL PERITONITIS IN LIVER CIRRHOSIS PATIENTS - HAROON, M; TARIQ, S; KHAN, MSN (Biological and Clinical Sciences Research Journal, 2022)
The aim of current analysis was to compare the efficacy of intravenous ciprofloxacin and ceftazidime for treating spontaneous bacterial peritonitis (SBP) in patients with liver cirrhosis. A retrospective study was conducted in the Medicine Department of SIMS, Lahore, from September 2021-September 2022. The study selected 110 cirrhosis patients with SBP were included in the study and were divided into two groups, A and B. Group A (n=55) was administered ciprofloxacin intravenously, and group B (n=55) was administered ceftazidime intravenously. The patients diagnosed with type 1 hepatorenal syndrome were treated with albumin and terlipressin daily. The clinical signs and causes of infection did not vary between both groups. The infection was resolved in 50 patients (90.9%) ceftazidime patients and in 51 patients (93%) ciprofloxacin patients. Out of 17 patients who developed, 10 patients (58.8%) completely recovered after terlipressin and albumin treatment, 1 (5.8%) showed partial response, and 6 (35.3%) did not respond. Switch therapy with ciprofloxacin and ceftazidime is equally effective in treating spontaneous bacterial peritonitis in cirrhotic patients with ascites.